Animal feeding and food safety. Report of a FAO Expert Consultation - Brufau J.; Tacon A. (Feed manufacturing in the Mediterranean region: Recent advances in research and technology, 1999)
The paper summarizes the findings of an FAO Expert Consultation on Animal Feeding and Food Safety held on 10-14 March 1997 in Rome, Italy. The report is divided into five main parts, namely: (i) the hazards associated with feed; (ii) assessment of risk; (iii) sources of feedborne hazards; (iv) control and feedborne hazards; and (v) conclusions and recommendations. The recommendations also include a draft code of practice for good animal feeding.
2. Conference of Feed Manufacturers of the Mediterranean, 1998/03/25-27, Reus (Spain)